1992
DOI: 10.1002/jab.770030109
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic bone cements: Residuals and extractability of methacrylate monomers and aromatic amines

Abstract: A new formulation of acrylic bone cement [methylmethacrylateln-decylmethacrylate/ isobornylmethacrylate (MMA/DMA/IBMA)] developed with the purpose of reducing the biologic adverse effects of bone cements was analyzed by high performance liquid chromatography for residual content of monomers and aromatic amines from the accelerator system [dimethyl-p-toluidine (DMPT), dihydroxypropyl-p-toluidine (DHPPT)] in the cured cement and for concentrations of these constituents in hydrophilic and lipophilic eluates. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…4,5 Boesch and coworkers 6 reported the presence of unreacted DMT (0.5-0.71%) in cements implanted over Acrylic bone cements are generally obtained by free radical periods of 2 to 10 years. Although the toxicity data on polymerization of methyl methacrylate (MMA) monomer DMT is scarce in the literature, 4,5,7 it is considered to be a in the presence of a solid phase consisting of poly(methyl highly toxic compound by inhalation and ingestion. Due methacrylate) (PMMA).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Boesch and coworkers 6 reported the presence of unreacted DMT (0.5-0.71%) in cements implanted over Acrylic bone cements are generally obtained by free radical periods of 2 to 10 years. Although the toxicity data on polymerization of methyl methacrylate (MMA) monomer DMT is scarce in the literature, 4,5,7 it is considered to be a in the presence of a solid phase consisting of poly(methyl highly toxic compound by inhalation and ingestion. Due methacrylate) (PMMA).…”
Section: Introductionmentioning
confidence: 99%
“…The methacryloyl derivative seemed to produce materials with accelerated ageing and less satisfactory mechanical properties when compared to the corresponding acryloyl derivatives. Trap et al 8 have developed a new bone cement (Boneloc) which contains dihydroxypropyl-4-toluidine as the activator. The new cement cured faster and more completely than the conventional Palacos R or Simplex RO.…”
Section: Tertiary Aromatic Amines Used In the Curing Of Acrylic Resinsmentioning
confidence: 99%
“…3 Boesch et al 4 reported the presence of DMT in quantities ranging from 0.05 to 0.71% in PMMA cements implanted for 2.5-10 years. Other studies 2,5,6 reported an average content of tertiary aromatic amines in the cured acrylic bone cements of 0.1-0.5 wt.%. On the other hand, tertiary aromatic amines are lowmolecular-weight compounds, which may leach out from the acrylic cement to the surrounding tissues.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, tertiary aromatic amines are lowmolecular-weight compounds, which may leach out from the acrylic cement to the surrounding tissues. 2,6 Stea et al 7 analyzed the release of DMT by high-performance liquid chromatography and demonstrated that there is a correlation between the amount of DMT released and the cytotoxic effects on the cell replication. Replication cycle is inhibited in short periods of time; however, DMT toxicity on cell cultures seems to be reversible and the cells do not die, but undergo a slackening in their replication cycle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation